Acceleration of radiation belt electrons and the role of the average interplanetary magnetic field Bz component in high‐speed streams. Issue 10 (17th October 2017) - Souza, V. M.; Lopez, R. E.; Jauer, P. R.; Sibeck, D. G.; Pham, K.; Da Silva, L. A.; Marchezi, J. P.; Alves, L. R.; Koga, D.; Medeiros, C.; Rockenbach, M.; Gonzalez, W. D.
Abstract: In this study we examine the recovery of relativistic radiation belt electrons on 15–16 November 2014, after a previous reduction in the electron flux resulting from the passage of a corotating interaction region (CIR). Following the CIR, there was a period of high‐speed streams characterized by large, nonlinear fluctuations in the interplanetary magnetic field (IMF) components. However, the outer radiation belt electron flux remained at a low level for several days before it increased in two major steps. The first increase is associated with the IMF background field turning from slightly northward on average to slightly southward on average. The second major increase is associated with an increase in the solar wind velocity during a period of southward average IMF background field. We present evidence that when the IMF B z is negative on average, the whistler mode chorus wave power is enhanced in the outer radiation belt, and the amplification of magnetic integrated power spectral density in the ULF frequency range, in the nightside magnetosphere, is more efficient as compared to cases in which the mean IMF B z is positive. Preliminary analysis of the time evolution of phase space density radial profiles did not provide conclusive evidence on which electron acceleration mechanism is the dominant. We argue that the acceleration of radiation belt electrons requires (i) a seed population of keV electrons injected into the inner magnetosphere by substorms and both (ii) enhanced whistler mode chorus waves activity as well as (iii) large‐amplitude MHD waves. Key Points: Slightly southward, on average, fluctuating IMF B z drives higher nightside ULF range‐integrated magnetic power spectral densities Slightly southward, on average, fluctuating IMF B z drives enhanced whistler mode chorus wave activity in the outer Van Allen belt Substorm‐injected electrons, large‐amplitude ULF fluctuations, and enhanced chorus wave power are important for outer belt electron flux recovery